Financiranje d.o.o. z lastnim kapitalom - Kocbek, Marijan (Podjetje in delo, 2016)
Law on commercial companies provides far different forms for financing of limited liability companies. Shareholders flnancing the company through new contributions obtain new or additional shares. Although financing the company through additional payments does not alter proportions among shareholders, additional payments strengthen a company 's liability potential toward creditors. Therefore, the article deals with legal, accounting, and tax aspects of additional payments.
Keywords: družbe z omejeno odgovornostjo; financiranje; gospodarske družbe; kapitalska razmerja; lastni kapital; poslovne finance